The Telephone Association of Canada Pavilion (Benjamin New Co., Ltd.)
The Telephone Association of Canada Pavilion attractions include this imaginative children's "Enchanted Forest", and an exciting film "Canada 67" in Circle-Vision 360 (Walt Disney Productions)